The Influence of Global Consumer Trends on Local Marketing Strategies in the Archipelago - Saputri, Fitri Arianti (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2025)
This article examines the impact of global consumer trends on local marketing strategies in the Indonesian archipelago, focusing on how changes in global consumer behavior affect marketing approaches in companies operating in Indonesia. Global consumer trends such as digitalization, sustainability, and personalization are increasingly influencing the local market, requiring companies to adapt their marketing strategies to remain relevant and competitive. This study uses qualitative and quantitative analysis methods by collecting data from in-depth interviews with marketing managers and consumer surveys to explore the impact of global trends on local marketing strategy decisions. The results show that companies in the Indonesian archipelago need to integrate global trends into their strategies, such as leveraging digital technology for marketing campaigns and adopting sustainable practices to attract consumers who are increasingly concerned about environmental issues. This article provides practical insights for local companies on how to adapt to global trends to increase competitiveness in the Indonesian market.